Does cognitive inflexibility predict violent extremist behaviour intentions? A registered direct replication report of Zmigrod et al., 2019. (22nd November 2021) - Schumann, Sandy; Salman, Nadine L.; Clemmow, Caitlin; Gill, Paul
Abstract: Purpose: Zmigrod et al. (2019a, Frontiers in Psychology, 10, 989) demonstrated that lower levels of cognitive flexibility predict a higher willingness to fight and die for the national in‐group. We conducted a registered direct replication of their Study 1. Extending the original study, we examined whether the documented relationship held when a self‐report measure for cognitive flexibility was introduced and when identity fusion was controlled for. We also investigated whether cognitive inflexibility predicts normative pro‐group behaviour intentions. Methods: Participants ( N  = 1378) reported in a cross‐sectional survey study their willingness to fight, die and sacrifice themselves for the in‐group and completed the Remote Associates (RAT) as and Wisconsin Card Sorting (WCST) tests. Afterwards, self‐reported cognitive flexibility, identity fusion and normative pro‐group behaviour intentions were assessed. Results: Results showed a small negative relationship between RAT accuracy rates and willingness to fight and die. WCST accuracy rates were positively related with willingness to die but not correlated with willingness to fight. Self‐report measures of cognitive flexibility were partially positively and partially negatively associated with support for violent extremism. There was further evidence that lower cognitive flexibility predicts higher normative pro‐group behaviour intentions. A mini meta‐analysis, which synthesized findings from the original study and our replication, demonstrated a relatively small negative correlation between cognitive flexibility and support for violent extremism. Conclusions: In summary, even though not all individual results could be replicated, we confirmed the overall conclusion of the original study: lower cognitive flexibility predicted stronger willingness to fight and die for an in‐group. The findings highlight that it is important to integrate cognitive style in multi‐level frameworks of risk factors of violent extremism. Additionally, our results point out that the validity of different measures of cognitive flexibility, including self‐report tools, must be further examined. Future research that evaluates cognitive flexibility training in the context of CVE/PVE interventions is also encouraged.